Pengaruh Attitude Towards Entrepreneurship terhadap Enterpreneurship Intention dengan Enterpreneurship Learning sebagai Moderasi pada Mahasiswa Jurusan Manajemen di IPB Internasional Bali - Anbarini, Ratih; Sitepu , Rismawati; Sarwoko, Endi; Darsana , Made (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2025)
This study aims to analyze the effect of attitude on entrepreneurial intention moderated by entrepreneurship learning in management students at IPB Internasional Bali. Using a quantitative approach with a survey design, data were collected from 100 fourth semester students and above through questionnaires and analyzed using the SEM-PLS technique. The results showed that attitude has a significant effect on entrepreneurial intention with an R-Square value of 0.871, but entrepreneurship learning does not significantly moderate the relationship (p-value = 0.491). These findings provide insight into the importance of attitude in shaping entrepreneurial intention and the role of entrepreneurship learning in the context of higher education at IPB Internasional Bali.